PENGELOMPOKKAN PADA KENDARAAN BERMOTOR MENURUT KEGUNAANNYA MENGGUNAKAN METODE DATA MINING K-MEANS - Windayani Pulungan; Poningsih Poningsih; Heru Satria (STMIK Budi Darma, 2019)
This study aims to look for the grouping of data in motor vehicles according to their use. The types of motorized vehicles in this study are ranging from motorbikes, cars, public transportation, taxis, public transportation, buses, and pick ups. In this case we need a method that can classify vehicle data according to its use. This research was conducted in Pematangsiantar and used the K-Means Data Mining method. K-Means method tries to group existing data into several groups, where data in one group has the same characteristics with each other and has different characteristics from the data in other groups. The highest cluster with the number of motorized vehicle data according to its use is 7 vehicles, namely, 3 wheels, Taxi, public transportation, Bus (public transportation), Truck / Pick Up (public transportation), Car, Truck / Pick Up (private transportation).Keywords: Data Mining, K-Means Method, Grouping of Motorized Vehicles.